Understanding the Current Health Services Research Workforce and Maximizing its Future. (21st September 2018) - Wolfe, Meghan J.; Simpson, Lisa A.; Menachemi, Nir
Abstract : In 2016, AcademyHealth continued its longstanding efforts to understand the health services research (HSR) workforce, to inform its changing needs through the commissioning of several papers and an invitational conference. This paper serves to summarize the commissioned studies that appear in the current issue of this journal.